In vitro evaluation of curcumin's antisickling activity and in silico analysis of curcuminoids and their ADMET properties - Clément M. Mbadiko; Koto-te-Nyiwa Ngbolua; Gédéon N. Bongo; Aristote P. Matondo; Jason T. Kilembe; Damien S. T. Tshibangu; Dorothée D. Tshilanda; Nadège K. Ngombe; Théophile F. Mbemba; Pius T. Mpiana (Discover Chemistry)
Abstract Background The aim of this study was to demonstrate the antisickling activity of curcumin and the in silico potential of curcuminoids and curcumin metabolites to inhibit HbS polymerization. Methods Emmel, osmotic, thermal fragility and F2+/Fe3+ ratio tests were carried out to display the antisickling potential. In silico screenings were carried out by molecular docking to determine the free enthalpies of complexation and to analyze the interactions between different ligands and HbS. MD simulations were carried out to examine the interactions of the three candidate drugs with the HbS enzyme, with the aim of confirming the structural stability of the ligand–protein complexes. Three molecules showed good docking scores during molecular docking were analyzed, namely: curcumin, cyclocurcumin and demethoxycurcumin. The in silico screening using the ADMET test was carried out to determine the pharmacokinetic profile of various compounds studied. Results In vitro screening showed that curcumin has an antisickling potential by inhibiting the formation of methamoglobin. The in silico screening revealed that all the ligands analyzed can form stable complexes with HbS; the binding energies of complexes formed between the ligands and HbS ranged from − 5.8 kcal/moL to − 8.1 kcal/moL. While the binding energies between curcumin glucuronide and cyclocurcumin with HbS were very stable compared with those of other compounds ( − 8.1 kcal/moL and − 8.0 kcal/moL respectively). Moreover, the findings revealed that some of the ligands analyzed can bind to the same sites on the receptors as the reference molecule. The RMSD diagrams of the three ligands in the complex with the HbS enzyme show that the three ligands selected for the MD simulations remain stable in their interaction with the protein for 100 ns. Of these, cyclocurcumin proved to be the most stable ligand in interaction with the receptor. The in silico toxicity screening showed that the majority of ligands fulfilled the Lipinski and Veber rules and would be less toxic; they would not pose absorption and permeability concerns. Conclusion Curcumin is a candidate in the treatment of sickle cell anaemia due its antisickling potential. This active ingredient can act alone or in synergy with other curcumin derivatives; and that the metabolites formed when curcumin is metabolized in the body can also inhibit HbS polymerization. Graphical abstract